Hubungan Tingkat Gejala Stres dengan Ide Bunuh Diri Pada Remaja SMA Negeri 1 Natar - Depri Wan Ramadan; Prima Dian Furqoni; Triyoso Triyoso; Rahma Elliya (Malahayati Nursing Journal, 2026)
ABSTRACT In the context of adolescent mental health, adolescence is a period full of challenges, where individuals experience various complex physical, emotional and social changes. Academic pressure, social problems, family conflicts and ethnic background. Can create a significant psychological burden for teenagers. Prolonged and poorly managed stress can have a profound impact on teenagers' mental health. When stress levels reach extreme points, some adolescents may develop maladaptive coping mechanisms, including suicidal thoughts or ideas as a response to the pressure they face. Objective: To determine the relationship between the level of stress symptoms and suicidal ideation in adolescents at SMA Negeri Natar. Quantitative research, using random sampling techniques with nonexperimental surveys. The population of this research is the entire class 12 at SMA Negeri 1 Natar in 2025 with a total of 420 students. Sample of 205 respondents. Using total simple random sampling technique. The data collection technique was carried out using a questionnaire. The data analysis used was Chi square. Based on the research conducted, the results showed that 54 (26.34%) respondents experienced low stress levels, 133 (64.87%) moderate stress and 18 (8.78%) high stress levels, then 31 (15.12%) had low levels of suicidal ideation, 156 (76.10%) had moderate suicidal ideation and 18 (8.78%) high suicidal ideation from a total of 205 (100%) respondents. The Chi Square test results obtained a P-value of 0.00 so it can be stated that there is a significant relationship between the level of stress and suicidal ideation in teenagers at SMA Negeri 1 Natar. Suggestion: It is hoped that schools and parents will be more active in providing emotional support to teenagers, as well as monitoring stress symptoms that arise so that suicidal ideation can be prevented from an early age.  Keywords: Stress in High School Adolescents, Suicide Ideas, Students.  ABSTRAK Dalam konteks kesehatan mental remaja, Masa remaja adalah periode yang penuh tantangan, di mana individu mengalami berbagai perubahan fisik, emosional, dan sosial yang kompleks. Tekanan akademis, masalah sosial, konflik keluarga serta latar belakang suku. Dapat menciptakan beban psikologis yang signifikan bagi para remaja. Stres yang berkepanjangan dan tidak terkelola dengan baik dapat memengaruhi kesehatan mental remaja secara mendalam. Ketika tingkat stres mencapai titik yang ekstrem, beberapa remaja mungkin mengembangkan mekanisme koping yang maladaptif, termasuk munculnya pikiran atau ide bunuh diri sebagai salah satu bentuk respons terhadap tekanan yang dihadapinya. Tujuan: Diketahui hubungan Tingkat gejala stress dengan ide bunuh diri pada remaja di SMA Negri Natar. Penelitian kuantitatif, menggunakan teknik random sampling dengan survei non eksperimen. Populasi penelitian ini adalah keseluruhan kelas 12 di SMA Negri 1 Natar tahun 2025 dengan jumlah 420 siswa. Sampel 205 responden. Dengan menggunakan teknik total simple random sampling. Tehnik pengumpulan data dilakukan dengan menggunakan quesioner. Analisa data yang digunakan adalah Chi square. Berdasarkan penelitian yang dilakukan di dapatkan hasil responden yang mengalami tingkat stres rendah 54 (26,34%) stres sedang 133 (64,87%) dan stres tinggi 18 (8,78%) lalu tingkat ide bunuh diri rendah 31 (15,12%) ide bunuh diri sedang 156 (76,10) dan ide bunuh tinggi 18 (8,78%) dari total 205 (100%) responden. Hasil uji Chi Square didapatkan nilai P-value 0,00 sehingga dapat dinyatakan bahwa ada hubungan yang bermakna antara tingkat stress dengan ide bunuh diri pada remaja SMA Negri 1 Natar. Saran: Diharapkan pihak sekolah dan orang tua siswa lebih aktif dalam memberikan dukungan emosional kepada remaja, serta melakukan pemantauan terhadap gejala stres yang muncul agar ide bunuh diri dapat dicegah sejak dini.  Kata Kunci: Stress Pada Remaja SMA, Ide Bunuh Diri, Siswa.